Types of approaches to mindfulness in young adults. Insights from original research - Dębska, Ewa (Rocznik andragogiczny, 2025)
With the increasing interest in mindfulness (mindful presence) across various areas of human functioning, this paper presents findings from qualitative research on the understanding and practice of mindfulness among individuals in early adulthood. Considering both theoretical and practical aspects, four types of approaches to mindfulness are identified. Type A individuals can describe what mindfulness is and practise it; Type B individuals can describe what mindfulness is but do not practise it; Type C individuals cannot describe what mindfulness is but practise it; and Type D individuals cannot describe what mindfulness is and do not practise it. W związku z coraz większym zainteresowaniem uważnością (uważną obecnością) w wielu obszarach funkcjonowania człowieka autorka przedstawia wyniki badań jakościowych dotyczących rozumienia pojęcia uważności i jej praktykowania przez osoby w okresie wczesnej dorosłości. Uwzględniając aspekty teoretyczne i pragmatyczne uważności, autorka tworzy typy podejścia do uważności: typ A – potrafi określić, czym jest uważność, i ją praktykuje; typ B – potrafi określić, czym jest uważność, ale jej nie praktykuje; typ C – nie potrafi określić, czym jest uważność, ale ją praktykuje; typ D – nie potrafi określić, czym jest uważność, i jej nie praktykuje.